Enseñanza de la fracción y la estructura aditiva en niños y niñas de grado sexto. una propuesta didáctica. (2020)
This work presents a didactic proposal for the teaching of the additive structure of fractions based on the problem solving method of Guzmán (1994) to contribute to the numerical thinking of sixth grade students. The idea arose from practices one and two that I did at the Liceo Femenino Mercedes Nariño with the ninth grade students, where flaws in algorithmic procedures in mathematics, especially those related to fractions, were evident.